Using the Four-Frame Leadership Approach to Mobilize Strategic Science Communication Efforts - Christine Krebs; Matthew Sowcik; Jamie Loizzo (EDIS)
This publication outlines some organizational strategies to consider when participating in science communication through the lens of Bolman and Deal’s four-frame leadership approach. Written by Christine Krebs, Matthew Sowcik, and Jamie Loizzo, and published by the UF/IFAS Department of Agricultural Education and Communication, March 2024.